Multi level authentication mechanism for grid application using one-time password - Behnia, Armaghan (2013)
Grid applications often involves large amount of data that requires secured resources access and sharing. The multi-institutional nature of a Grid environment introduces challenging security issues, especially with regard to authentication. The goal of this project is to propose an advance authentication mechanism which will furnish users with more secured and also practical environment. Although there are different available mechanisms such as PKI, KX.509, Kerberos, One-Time password and etc., proposing a Multi-level mechanism to provide better security and more reliability still is in demand. However a large number of the existing mechanisms used X.509 certificate, beside all its advantages due to its long period of validity it may compromise through brute force attacks or dictionary attacks. In order to come up with a solution to this vulnerability, this project attempts to propose an advance mechanism by three different levels. Experiments show the structure is flexible and it can improve efficiency and reduce the risk of dictionary attack